Survival Mechanisms of Clarias batrachus: Glycogen Utilization During Long-Term Starvation - Prasad, Nayan K.; Shachi, Kumari; Kumar, Sanjeev; Sahani, Suresh Kumar (Darul Yasin Al Sys, 2024)
This study aims to analyze the impact of extended food deprivation on glucose storage in different tissues and organs of the freshwater air-breathing catfish Clarias batrachus. The glycogen reserves in the brain, gonads, liver, muscles, and blood of both the male and female Clarias batrachus were estimated after forty days of starvation. The total glycogen was determined by a modification of the colorimetric method of Krishnaswami & Srinivasan in collaboration with Kemp and Heijningen. Even though they had to endure the severe deprivation of food, Clarias batrachus survived during the entire period of experimentation. Nutrient deprivation due to fasting gradually depletes glycogen reserves to a minimal level in all organs. This is partly caused by increased transamination and deamination processes, partly by the inhibition of RNA synthesis, and perhaps becomes increasingly significant during long-term starvation through gluconeogenesis. Importantly, during the first 20 days of starvation, the concentration of glycogen in the brain did not change noticeably in contrast to the liver, muscles, and gonads, which decreased glycogen stores significantly. The fall in blood glucose levels followed a decline in liver and muscle glycogen stores. Glycogen concentration in the liver was higher than in other solid tissues such as muscle, brain, and gonads. Females were observed to have higher glucose stores in all tissues than males when expressed per unit body mass in normal and starvation conditions. After forty days of starvation, the most substantial decrease in glycogen content was observed in the testes, while the brain exhibited the minimum decrease.